Biopsychosocial approach to tendinopathy - Christopher Clifford; Paul Kirwan; Neal L Millar; Seth O'Neill; Carles Pedret; Nathan Edgar (BMJ Open Sport & Exercise Medicine, 2022)
Tendinopathy describes a spectrum of changes that occur in damaged tendons, leading to pain and reduced function that remains extremely challenging for all clinicians. There is an increasing awareness of the influence that psychological and psychosocial components, such as self-efficacy and fear-avoidance, have on rehabilitation outcomes in musculoskeletal medicine. Although it is widely accepted that psychological/psychosocial factors exist in tendinopathy, there is currently a distinct lack of trials measuring how these factors affect clinical outcomes. Biopsychosocial treatments acknowledge and address the biological, psychological and social contributions to pain and disability are currently seen as the most efficacious approach to chronic pain. Addressing and modulating these factors are crucial in the pathway of personalised treatments in tendinopathy and offer a real opportunity to drive positive outcomes in patients. In this education review, we also provide the current evidence-based guidance on psychological and psychosocial developments in musculoskeletal medicine and how these may be translated to treating tendinopathy using a biopsychosocial model.